Carotid intima-media thickness in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil): a narrative review - Santos, Eduardo Henrique Sena; Santos Neto, Pedro José dos; Santos, Itamar de Souza (São Paulo Medical Journal, 2018)
BACKGROUND: Carotid intima-media thickness (CIMT), as measured by ultrasound, has been used in large studies as a non-invasive marker for subclinical atherosclerosis. The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) is a cohort of 15,105 civil servants in six Brazilian cities that included CIMT evaluation in its baseline assessment. The aim of the present narrative review was to provide an overview of ELSA-Brasil CIMT articles published up to July 31, 2017. DESIGN AND SETTING: Narrative review of ELSA-Brasil CIMT studies using baseline assessment data. METHODS: We searched PubMed for the terms “ELSA-Brasil” and “intima-media”. This search yielded 21 published articles using CIMT data from the ELSA-Brasil baseline assessment, which were included in this review. We also present information about intima-media thickness assessment from ongoing onsite reevaluations of the study participants. RESULTS: Most published studies focused on the association with traditional and novel cardiovascular riskfactors. Studies also presented information about the ELSA-Brasil CIMT protocol at baseline and CIMT value distribution in this large sample. CONCLUSIONS: Analyses on the ELSA-Brasil data led to important insights on CIMT interpretation and physiology. Besides the highlighted contributions which have already been made in this field, new data gathered during the ongoing third onsite assessment will enable investigation of substantially new research questions.